Stress memory and epigenome variations: insights into the thermal tolerance potential of Cladocora caespitosa (Linnaeus, 1767), a Mediterranean hermatypic coral - Bisanti, Luca; La Corte, Claudia; Dara, Mariano; Bertini, Federica; Rizzuto, Gabriele; Valenti, Rossella; Naselli, Flores; Parrinello, Daniela; Parisi, Maria Giovanna; Tomasello, Agostino; Caradonna, Fabio; Chemello, Renato; et al. (Frontiers in Marine Science, 2025)
Stress memory is a key ecological and evolutionary response for sessile organisms under changing environmental conditions, but the ubiquity of this phenomenon among coral species and habitat is unknown. We exposed colonies of the Mediterranean coral Cladocora caespitosa to two short-term thermal profiles (constant high and pulse) and quantified the genome-wide DNA methylation level before stress testing 75 days later. Here we show that a protective effect could be induced using short-term thermal profiles, which significantly improved immune tolerance and bleaching resistance. We found a significant relationship between genomic methylation levels and accumulated thermal stress by corals, preliminarily suggesting an epigenetic regulation dynamic of temperate coral tolerance in response to climate change. Our results represent new mechanistic insights into the stress memory of Mediterranean corals, supporting a role for DNA methylation in crucial cryptic complexity of plasticity avenues.